I am Closer to Friends, I Feel Worthy: Santriâ€™s Peer-Attachment and Self-Esteem - Ringganis, Khoyrinnisa; Darmayanti, Kusumasari Kartika Hima (Jurnal Psikologi Islam dan Budaya, 2023)
The environment in Islamic boarding schools makes students feel closer to their peers. When students have closeness with peers, they will feel good emotional attachment and affect their self-esteem. This study aims to determine the effect of peer-attachment on students' self-esteem. This study used a correlational quantitative approach. The participants were 174 students aged 12-19 years from Islamic boarding schools in the city of Palembang, obtained through a purposive sampling technique. Data analysis used a simple linear regression technique. This study found that peer-attachment affects self-esteem by âˆ†R2 = 3.96%. Therefore, teachers and pesantren authorities must pay attention to peer attachment to increase self-esteem among students, because good peer attachment will increase students' self-esteem. The results show a significant positive effect and emphasize that students who have attachment to peers can have a more positive self-assessment.